In silico Exploration of the Therapeutic Potential of Alkaloids as Anti-infective Agents - Rani, Nidhi; Kumar, Praveen; Walia, Aditya; Singh, Randhir (Letters in Drug Design & Discovery, 2024)
BackgroundAlkaloids are important phytoconstituents obtained from various plant sources.MethodsThe main objective of the study was to evaluate the anti-infective potential of alkaloids against 14α-demethylase, transpeptidase, and omicron spike protein using molecular docking studies. The potential constituents were identified and an ADMET study was performed.ResultsThe study concluded that reserpine and tubocurarine exhibited potential activity against the three tested enzymes with good ADMET profile.ConclusionReserpine and tubocurarine can further be explored to attain new candidates as anti-infective agents.
Keywords: 14α-demethylase